Intersectionality, nationalisms, biocoloniality - Narayan, Yasmeen (Ethnic and racial studies, 2019)
The early twenty-first century is marked by new postcolonial nationalist ideologies and their indifference to modern histories of colonisation and the urgent need for anti-nationalist theories of racialised subjectification. I discuss the importance of work on 'intersectionality' and consider how some theoretical formations reproduce core elements of 'common sense' nationalisms such as universal, fixed racial categories, the gender binary and the idea of separate cultures. I then argue for a transdisciplinary theory of racialised subjectivity that I call 'biocoloniality'.